Hepatic involvement in typhoid fever: Biochemical and histopathological study in anicteric patients - Salazar, Raúl (1995)
Retrospective study of 100 patients with diagnosis of typhoid fever by Salmonella typhi isolation. Main diagnostic procedure was bone marrow culture with 90% positivity. Hepatic involvement occurred in 85% patients, 67 without jaundice and 18 with jaundice. Fifty patients without jaundice had liver biopsy: 50% showed finding compatible with granulomatous hepatitis and 50% with reactional hepatitis. Response to antibiotics was similar in both patients with and without liver involvement.